2014
DOI: 10.5194/npg-21-451-2014
|View full text |Cite
|
Sign up to set email alerts
|

Regional and inter-regional effects in evolving climate networks

Abstract: Abstract. Complicated systems composed of many interacting subsystems are frequently studied as complex networks. In the simplest approach, a given real-world system is represented by an undirected graph composed of nodes standing for the subsystems and non-oriented unweighted edges for interactions present among the nodes; the characteristic properties of the graph are subsequently studied and related to the system's behaviour. More detailed graph models may include edge weights, orientations or multiple type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…The network is represented by its binary adjacency matrix A with entries A ij = 1 if two nodes i and j are linked and A ij = 0 otherwise [Donges et al, 2009b;Boers et al, 2013;Stolbova et al, 2014]. An extension of this procedure is the usage of an edge-weighted adjacency matrix W where W ij = 0 denotes the absence of a link, but W ij > 0 denotes its strength (e.g., the pairwise correlation) [Barrat et al, 2004;Hlinka et al, 2014;Zemp et al, 2014].…”
Section: Methodsmentioning
confidence: 99%
“…The network is represented by its binary adjacency matrix A with entries A ij = 1 if two nodes i and j are linked and A ij = 0 otherwise [Donges et al, 2009b;Boers et al, 2013;Stolbova et al, 2014]. An extension of this procedure is the usage of an edge-weighted adjacency matrix W where W ij = 0 denotes the absence of a link, but W ij > 0 denotes its strength (e.g., the pairwise correlation) [Barrat et al, 2004;Hlinka et al, 2014;Zemp et al, 2014].…”
Section: Methodsmentioning
confidence: 99%
“…The issue of interdependent predictors is not limited to pair-wise relationships: it has been shown that various variability modes in the climate system are intertwined in quite complex networks, with nontrivial time-delayed relations among oscillations in different regions (e.g., Wyatt et al, 2012). Intricacy of such structures becomes even more apparent when generalized links are studied, unrestricted to just the conventional variability modes (e.g., Hlinka et al, 2013Hlinka et al, , 2014a.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial scales for climate subsystems can be inferred from climate data using classical approaches of rotated principal component analysis combined with more recent surrogate data testing approach [58], or the very modern approach of complex networks [59]. Evolving climate networks can track important short-term climate influencing events such as El Niño episodes or large volcanic eruptions [60] and discern regional from global effects [61]. Besides considering specific spatial scales, a more detailed look on repetitive patterns on specific temporal scales in the air temperature and other meteorological data has led to an identification of oscillatory phenomena possibly possessing a nonlinear origin and exhibiting phase synchronization between oscillatory modes extracted either from different types of climate-related data or data recorded at different locations on the Earth [9][10][11][12][13]37].…”
Section: Cross-scale Information Transfer In Atmospheric Dynamicsmentioning
confidence: 99%